Pelatihan Pembuatan Perangkat Pembelajaran Harian (RPPH) menggunakan Tari Kreatif bagi Guru PAUD - Wulandari, Hayani; Muqodas, Idat; Maranatha, Jojor Renta; Nikawanti, Gia; Amalia, Hanny Anisa; Nadilah, Nur Alfat; Elzawati, Elzawati (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2022)
In the industrial era 4.0, all sectors are required to create new innovations, including education. However, the facts on the ground show that learning is still limited and monotonous. Meanwhile, early childhood is stimulated through interesting and fun activities. This training activity aims to provide new insights on the preparation of learning tools by combining creative dance learning. The method of implementation is done by providing material and direct practice. The number of participants who took part in the training activities were 6 educators and 3 students. The results of the training stated that all participants were able to follow all stages of activities and prepare daily lesson plans with creative dance lessons. Thus, it can be concluded that this training can have a positive impact on teachers so that they are motivated to develop lesson plans